Civic Education Learning Management and Its Impact on Students’ Character Building Based on Local Values - Muhamad Khatami Rafsanjani; Maemunah; zedi Muttaqin (Journal of Educational Management Research, 2026)
Strengthening students’ character is a strategic issue in education, particularly through Civic Education that integrates local cultural values to enhance contextual relevance and meaningfulness. However, empirical evidence regarding the effectiveness of Civic Education learning management in supporting character building remains limited. This study aims to analyse the effect of Civic Education learning management on strengthening students’ character based on local values in private schools, as well as to identify relevant local cultural elements that can be integrated into Civic Education learning. This study employed a quantitative approach using a survey method involving 153 students selected through a snowball sampling technique. Data were collected using a Likert-scale questionnaire consisting of 25 statements. The data were analysed using descriptive statistics and regression analysis with the assistance of SPSS software. The results indicate that Civic Education learning management has a significant and positive effect on strengthening students’ character based on local values, with a coefficient of determination (R²) of 41.4% and a significance value of 0.000 (p < 0.05). These findings imply that well-planned, systematic, and integrated management of Civic Education learning that incorporates local cultural values plays a crucial role in fostering students’ character development in a contextual and sustainable manner.